Phenotypical T Cell Differentiation Analysis: A Diagnostic and Predictive Tool in the Study of Primary Immunodeficiencies - Attardi, Enrico; Di Cesare, Silvia; Amodio, Donato; Giancotta, Carmela; Cotugno, Nicola; Cifaldi, Cristina; Chiriaco, Maria; Palma, Paolo; Finocchi, Andrea; Di Matteo, Gigliola; Rossi, Paolo; Cancrini, Caterina (Frontiers in Immunology, 2019)
Multiparametric flow cytometry (MFC) represents a rapid, highly reproducible and sensitive diagnostic technology for primary immunodeficiencies (PID), which are characterized by a wide range of T cell perturbations and a broad clinical and genetic heterogeneity. MFC data from CD4+ and CD8+ T cell subsets were examined in 100 patients referred for Primary Immunodeficiencies to our center. Principal component analysis (PCA), a non-hypothesis driven statistical analysis, was used to analyze MFC data in order to distinguish the diverse PIDs. Among severe lymphopenic patients, those affected by severe combined and combined immunodeficiency (SCID and CID) segregated in a specific area, reflecting a homogenous and a more severe T cell impairment, compared to other lymphopenic PID, such as thymectomized and partial DiGeorge syndrome patients. PID patients with predominantly antibody defects were distributed in a heterogeneous pattern, but unexpectedly PCA was able to cluster some patients’ resembling CID, hence warning for additional and more extensive diagnostic tests and a diverse clinical management. In conclusion, PCA applied to T cell MFC data may help the physician to estimate the severity of specific PID and to diversify the clinical and diagnostic approach of the patients.